Pelatihan Jurnalistik Warga Bagi Pemuda Karang Taruna - Endri Listiani; Wiki Angga Wiksana (MENARA RIAU, 2022)
Media news content, often seems to be separated from the public interest or public interest. The public interest has not yet become mainstream in the editorial work routine. Until finally, citizen journalism emerged as a complement to public journalism which so far has often only been a tool for the interests of certain groups. Through this model of citizen journalism, it is hoped that public apathy can be replaced with full participation. Moreover, coupled with very rapid technological advances, it accelerates the development of citizen journalism because it facilitates citizen participation. To prepare this citizen journalism, it is necessary to prepare the community's ability in basic journalistic skills. Until their writing becomes fit for consumption. Therefore, this citizen journalism training was held, especially at the youth organization in desa Lamajang, kec. Pangalengan, kabupaten Bandung, who had an interest in developing writing skills and a desire to develop their village. Improving the ability of youth who will become the next generation is a must. To maximize citizen journalism, preparing young people who are media literate is an asset. Being a very valuable asset, this young man has the provision of qualified media skills.